Robust control of a two-terminal cryogenic current comparator - Bierzychudek, Marcos Eduardo (2013)
A digital H controller for a two-terminal cryogenic current comparator is designed. To this end, a set of mathematical models covering the actual system is proposed. Simulation results compare the open-and closed-loop systems based on the proposed controller and the traditional integral control. According to these results, the new controller can significantly reduce the noise in the superconducting quantum interference device sensor.